2012
DOI: 10.1590/s0103-64402012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effects of chitosan on dentin structures

Abstract: Complete debridement with smear layer removal are essential measures for achieving a successful outcome of root canal treatment. The aim of this study was to evaluate the effects of chitosan at different concentrations on the removal of the smear layer and on dentin structure after 3 and 5 min of application. Twelve recently extracted maxillary canine teeth were instrumented using the crown-down technique and irrigated with 1% sodium hypochlorite. The specimens were distributed according to the time and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
1
31

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 22 publications
4
95
1
31
Order By: Relevance
“…Pimentaet al [44] reported that the 0.2% chitosan solution (pH=3.2) has a capacity to reduce dentin microhardness similar to that of 15% EDTA (pH=7.25) representing similar demineralization potential. The effect of 0.2% chitosan applied for 3 minutes was the most effective for removing the smear layer and smear plug with minimal erosive effect on dentin substrate as suggested previously in the study of Silva et al [38].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Pimentaet al [44] reported that the 0.2% chitosan solution (pH=3.2) has a capacity to reduce dentin microhardness similar to that of 15% EDTA (pH=7.25) representing similar demineralization potential. The effect of 0.2% chitosan applied for 3 minutes was the most effective for removing the smear layer and smear plug with minimal erosive effect on dentin substrate as suggested previously in the study of Silva et al [38].…”
Section: Discussionsupporting
confidence: 66%
“…The most reported causes of their failure are retention loss or marginal degradation [39]. Many factors were proposed to be involved in bond degradation and different methods were used to reproduce clinical situations and simulate the oral environment in order to test the dentin bonding durability [37,38]. Among these methods, thermal cycling, load cycling and prolonged water or artificial saliva incubation were commonly used [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, endodontic irrigants may alter the physicochemical properties of dentin (3,9). NaOCl causes oxidation of the organic matrix and denaturation of collagen, changing the chemical structure of dentin and affecting its mechanical properties (10).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the decalcification properties of two chelators were evaluated when associated with different protocols of agitation. Chelating agents play an important role in the process of removing smear layer, as they increase dentin permeability [23, 24]. We assessed the effectiveness of two chelating substances (0.2% Chitosan and 17% EDTA) based on the amount of Calcium ions released, using atomic absorption spectrometry.…”
Section: Discussionmentioning
confidence: 99%